What is public health? a scoping review - Razieh Azari; Bettina Borisch (BMC, 2023)
Abstract Background during the last hundred years, several major public health issues have already afflicted humanity. Most frequently cited definitions of public health have stemmed from long-standing definitions, which raises several concerns including whether these definitions can respond to today's public health challenges. The present study aimed to identify and review available public health definitions in the first place. Methods in this scoping review, we undertook an electronic search in four databases (PubMed, Web of Science, Embase, and EBSCOhost) from inception until June 06, 2022, and a grey literature search in Google Scholar. Moreover, reference lists of publications included in the scoping review were screened manually for additional relevant publications. All types of scientific publications, in English, that focused on the definition of public health and provided an original definition were included. Year, type, disciplinary fields of publications, objectives of publications, and public health definitions were extracted. Results 5651 publications were identified through the scoping search, of which five were subjected to full-text review. Of these publications, two were included. An additional nine publications were identified through the manual screening. A total 11 of publications were included in the scoping review. Of the 11 definitions included in this review, the latest original definitions date back to about two decades ago. Conclusions there is a noticeable lack of updated definitions of public health. Considering our findings and the ever-changing nature of public health issues, there is an urgent need for re-assessing and updating public health definitions.